Cosmogenic radionuclide dating of glacial landforms in the Lahul Himalaya, Northern India: defining the timing of Late Quaternary glaciation - Owen, LA; Gualtieri, L; Finkel, RC; Caffee, MW; Benn, Douglas Iain; Sharma, MM (2001)
The timing of glaciation in the Lahul Himalaya of northern India was ascertained using the concentrations of cosmogenic Be-10 and Al-26 from boulders on moraines and drumlins, and from glacially polished bedrock surfaces. Five glacial stages were identified: Sonapani I and II, Kulti, Batal and Chandra. Of these, cosmogenic exposure ages were obtained on samples representative of the Batal and Kulti glacial cycles. Stratigraphical relationships indicate that the Sonapani I and II are younger. No age was obtained for the Chandra glacial advance. Batal Glacial Stage deposits are found throughout the valley, indicating the presence of an extensive valley glacial system. During the Kulti Stage, glaciers advanced ca. 10 km beyond their current positions. Moraines produced during the Batal Stage, ca. 12-15.5 ka, are coeval with the Northern Hemisphere Late-glacial Interstadial (Bolling/Allerod). Deglaciation of the Batal Glacial Stage was completed by ca. 12 ka and was followed by the Kulti Glacial Stage during the early Holocene, at ca. 10-11.4 ka. On millennial time-scales, glacier oscillations in the Lahul Himalaya apparently reflect periods of positive mass-balance coincident with times of increased insolation. During these periods the South Asian summer monsoon strengthened and/or extended its influence further north and west, thereby enhancing high-altitude summer snowfall. Copyright (C) 2001 John Wiley & Sons, Ltd.